Milk Production, Lactation Curve and Persistency of Friesian Holstein Cows in Smallholder Dairy Farms - Ridhowi, Aswah; Djoharjani, Trianti; Maylinda, Sucik (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2026)
This study aimed to evaluate milk production, lactation curve characteristics, and lactation persistency of Friesian Holstein cows reared under tropical smallholder dairy farming conditions. Milk production data were collected from 164 lactating cows across five lactation periods during a 305-day lactation. Cows were milked twice daily, and weekly average milk yields were used to describe lactation curves and persistency patterns. The results showed that milk production increased progressively from the first to the third lactation and declined during the fourth and fifth lactations. The highest total milk production was observed in the third lactation (5539.6 L), while the first lactation showed the lowest yield (3649.1 L). All lactation groups exhibited a typical lactation curve pattern, characterized by rapid milk yield increase after calving, peak production during weeks 4 – 7, and gradual decline thereafter. Lactation persistency was better in first- and second-lactation cows less than 8%, with lower monthly production declines compared to older cows. Milk production decline accelerated 9.25% after five months of gestation, indicating reduced persistency during late pregnancy. Incorporating lactation period and gestation stage into nutritional and reproductive management programs may help optimize milk production and lactation persistency. Such strategies can contribute to improved productivity and economic efficiency in tropical smallholder dairy farms.